EFFECTIVENESS OF AI-GENERATED LISTENING MATERIALS VS. TEXTBOOK AUDIO IN EFL LEARNING - Baxramova Malika Muzaffarovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This study examines the comparative effectiveness of AI-generated listening materials and traditional textbook audio in the context of English as a Foreign Language (EFL) learning. With the growing use of Artificial Intelligence in language education, learners are increasingly exposed to dynamic, customizable, and context-specific audio content generated by advanced text-to-speech technologies. This article analyzes  how  such  AI-driven  resources  impact  listening  comprehension,  learner engagement, and pedagogical flexibility compared to scripted, professionally recorded textbook audio. Drawing on theoretical perspectives and recent empirical findings, the paper  explores  dimensions  such  as  adaptability,  content  authenticity,  listening accuracy,  and  learner  motivation.  While  AI-generated  materials  offer  greater personalization and relevance to real-world communication, textbook audio provides structured, predictable input that aligns closely with curriculum goals. The findings suggest that a blended model combining both modalities may yield optimal results, balancing  innovation  with  pedagogical  consistency.  The  study  highlights  the importance  of  integrating  technological  advancements  thoughtfully  to  enhance listening proficiency while supporting diverse learner needs and preferences.